Using Meta-1-The 1st Version of the UMLS Metathesaurus - Tuttle, Mark (1990)
The National Library of Medicine (NLM) is developing the Unified Medical Language System (UMLS) to provide uniform access to the world's biomedical knowledge. The foundation of the UMLS is a metathesaurus of concept names, or terms. Meta-1, the first version of the Metathesaurus, was synthesized from existing biomedical nomenclatures and classification systems, and it contains in excess of 100,000 terms, including all those from MeSH and DSM, and a portion of those from SNOMED, ICD, CPT, LCSH, COSTAR and other sources. These names are arranged and labeled so as to help answer the questions, “What is it called?” and “Where can I find out more about it?” We refer to the first question as the naming problem, and the second as the location problem, respectively. We think of Meta-1 as a source of lexical diversity and semantic locality with which to address these problems in biomedicine. While the NLM will be using Meta-1 in the UMLS, non-NLM developers and users may wish to use Meta-1 to help solve their own naming and location problems